Sosialisasi Pengenalan dan Pencatatan Akuntansi pada Kelompok Tani Kelurahan Maharatu - Nuraini Nuraini; Desiyanti Rifayani; Nadia Triwahyuni; Nisa Alqorni (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aimed to enhance the knowledge and skills of members of the Maharatu Urban Farmer Group in Pekanbaru regarding basic financial recording and bookkeeping. The method employed was a socialization and counseling approach to introduce the importance of simple financial documentation. A total of 25 participants, all members of the farmer group, took part in the activity. The results indicate that the participants gained a clear understanding of basic accounting principles and the practice of simple bookkeeping. Furthermore, they recognized the importance of separating household finances from agricultural business finances, which is crucial for better financial management in farming operations.